Catalytic Ozonation of Biologically Treated Leachate from Municipal Solid Waste in a Microbubble Reactor. (3rd September 2019) - Huang, Xiaoxue; Cheng, Wen; Quan, Xuejun; Cheng, Chen; Cheng, Zhiliang; Yang, Lu
ABSTRACT: Catalytic ozonation using activated carbon (AC) as catalyst for advanced treatment of biologically treated leachate (BTL) from municipal solid waste incineration plant was carried out in a microbubble reactor. The removal efficiency of chemical oxygen demand (COD) in the leachate was significantly improved over that in the conventional bubble reactor. The effects of AC dosage, ozone concentration, ozone flowrate and liquid reaction temperature on COD removal efficiency were studied. The results show that the COD removal efficiency increased with increasing AC dosage, ozone flowrate and inlet ozone concentration, and the reactor liquid phase temperature has little effects on the COD removal efficiency. The maximum COD removal efficiency reached 89.87% in the AC/O3 system under the optimal conditions. The catalytic activity of the AC still remained stable after five cycles of use. Ultraviolet-visible (UV-Vis) spectra and GC-MS analysis indicated that the AC-catalyzed ozonation can enhance the efficiency of the organic pollutants; the mechanism of AC deactivation was explored using the variation of AC-specific surface area and X-ray diffraction analysis. In addition, the regeneration of AC was proved effective by hydrochloric acid leaching. These results show that the combination of a microbubble reactor with AC provided a highly efficient ozonation process for the BTL.